Front Cover: Small‐Molecule Activation by Heteroleptic Metallasilylenes (Eur. J. Inorg. Chem. 2/2023). Issue 2 (21st December 2022) - Schoening, Juliane; Wölper, Christoph; Schulz, Stephan
Abstract : The Front Cover illustrates the outcome of selected small molecule activation reactions using heteroleptic metallasilylenes L 1 (Cl)MSiL 2, which are represented by the basic cards. By adding a "reACTION card", displaying the small molecules CO2, N2 O, or Me3 SiN3, on top of a basic card, the corresponding "product cards", which symbolize the resulting carbonate complexes, silanoic esters, and silaimine, have to be found and placed on the matching top card. This game can be enjoyed in a friendly atmosphere with a glass of wine. More information can be found in the Research Article by S. Schulz and co‐workers .